2017
DOI: 10.1007/s11102-017-0804-z
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid sinus mucosal thickening in the acute phase of pituitary apoplexy

Abstract: PurposeIn pituitary apoplexy (PA), there are preliminary reports on the appearance of sphenoid sinus mucosal thickening (SSMT). SSMT is otherwise uncommon with an incidence of up to 7% in asymptomatic individuals. The aim of this study was to evaluate the incidence and clinical significance of SSMT in patients with PA and a control group of surgically treated non-functioning pituitary adenomas (NFPAs).MethodsRetrospective review of clinical and imaging variables in PA and NFPA patients. Sphenoid sinus mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
(38 reference statements)
0
22
0
1
Order By: Relevance
“…The identification of known respiratory pathogens from the sinuses of PA patients could be indicative of an infective aetiology. In support of this is the observation of increased prevalence of sphenoid sinus mucosal thickening in patients presenting with PA, most notably within the first week of the onset of symptoms [ 2 , 17 , 18 ]. Infection is also a known risk factor for other cerebral vascular phenomena, such as cavernous sinus syndrome [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The identification of known respiratory pathogens from the sinuses of PA patients could be indicative of an infective aetiology. In support of this is the observation of increased prevalence of sphenoid sinus mucosal thickening in patients presenting with PA, most notably within the first week of the onset of symptoms [ 2 , 17 , 18 ]. Infection is also a known risk factor for other cerebral vascular phenomena, such as cavernous sinus syndrome [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…We and others have observed a high incidence of abnormal sphenoid sinus changes in PA [ 2 ]. In a recent study we noted that sphenoid sinus mucosal thickening (SSMT) was present in 62% of PA patients compared to just 6% of a control group of non-functioning pituitary adenomas (NFPAs) [ 2 ]. The aetiology of SSMT in PA is unknown and possibilities include inflammation or infection.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative MRI scans were reviewed by SR and DB to determine lesion volume as described previously (4/3 × : × radius 3 ) [14].…”
Section: Imaging Reviewmentioning
confidence: 99%
“…In pituitary apoplexy patients, some authors reported the thickening of the sphenoid sinus mucosa related to venous engorgement in this region as an excellent sign that is present from the early stage, a reversible condition on follow-up studies that generally improves spontaneously [104]. This thickening does not indicate infectious sinusitis and thus does not rule out the surgical transsphenoidal route [103,105].…”
Section: Pituitary Imagingmentioning
confidence: 99%
“…Some published series have demonstrated the great value of special techniques as T2-weighted gradient echo to detect pituitary hemorrhage in the acute phase and chronic phase. MRI diffusion-weighted images (DWI) can be also be helpful in rare cases of ischemic pituitary necrosis without hemorrhage [105][106][107].…”
Section: Pituitary Diseasesmentioning
confidence: 99%